2021
DOI: 10.18203/2349-2902.isj20210920
|View full text |Cite
|
Sign up to set email alerts
|

RIPASA score or Alvarado score: diagnosing acute appendicitis

Abstract: Background: Appendicitis is a much studied about topic since the early years. Even with the advances in imaging techniques, appendicitis still relies upon clinical examination as a main resort of diagnosis. To aid this, several scoring systems have been developed taking into account various symptoms, signs and some basic laboratory investigations. Many studies have been done worldwide to check the sensitivity and specificity of each of these clinical scoring systems in the diagnosis of acute appendicitis. Thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…reported that the sensitivity of RIPASA score was more highly than Alvarado (100% vs. 60.8%, respectively). 14 consistent with our findings, Parmeshwar et al 15 reported sensitivity of 94.73% for RIPASA scoring system and 67.36% for Alvarado that was closed to our findings (67.1% vs. 67.36%). Next, we evaluated the specificity of scoring systems.…”
Section: Discussionsupporting
confidence: 93%
“…reported that the sensitivity of RIPASA score was more highly than Alvarado (100% vs. 60.8%, respectively). 14 consistent with our findings, Parmeshwar et al 15 reported sensitivity of 94.73% for RIPASA scoring system and 67.36% for Alvarado that was closed to our findings (67.1% vs. 67.36%). Next, we evaluated the specificity of scoring systems.…”
Section: Discussionsupporting
confidence: 93%